ANALISA POSTUR KERJA PADA BAGIAN PEMBOTOLAN LIMUN DENGAN METODE QUICK EXPOSURE CHECK - hendra antony hutabarat; eddy eddy; nismah panjaitan (Universitas Harapan Medan, 2020)
PT. PabrikEsSiantar is a factory that produces bottled drinks. As an industry which is also a labor-intensive industry where there are many manual material handling activities carried out by workers. The large number of manual material handling jobs is feared to cause musculoskeletal disorders (MSDs), namely complaints in the parts of the skeletal muscles that a person feels ranging from very mild complaints to very pain arising from awkward postures by the body when working. This research method uses the Quick Exposure Check method, which is the assessment by combining the assessment from the perspective of the researcher based on the observed posture of the worker and based on the assessment by the worker. Then recapitulate the questionnaire data in the QEC score sheet and determine the value of the exposure score, the score obtained is 45 - 53 with an exposure percentage of 50 - 58%, so further research and changes are needed. The proposed work posture improvement design is suggested to pay attention to risk factors, especially the back so as not to bend over